2003
DOI: 10.1590/s0100-879x2003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Vertical growth phase and positive sentinel node in thin melanoma

Abstract: Sentinel node (SN) status is the most important prognostic factor for localized melanoma. Usually, patients with Breslow thickness of less than 1.0 mm are not included in SN protocols. However, the literature presents a rate ranging from 3 to 7% of nodal recurrence in thin melanoma. Ulceration, regression and high mitotic rate have been considered to be indications for an SN biopsy. The metastatic potential of the vertical growth phase is uncertain. To correlate pathological features in thin melanoma with SN m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 18 publications
6
60
0
6
Order By: Relevance
“…However, several authors have reported their experience in SNB in thin melanoma patients [36,[42][43][44][45][46][47][48][49] (Table V).…”
Section: Discussionmentioning
confidence: 99%
“…However, several authors have reported their experience in SNB in thin melanoma patients [36,[42][43][44][45][46][47][48][49] (Table V).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] When regional nodes are involved, survival rates are roughly halved. However, within stage III, 5-year survival rates range from 20% to 70%, depending primarily on the nodal tumor burden.…”
mentioning
confidence: 99%
“…5,6 Vertical growth phase, high mitotic rate, and regression are other factors that may increase the risk of recurrence or metastasis of melanoma. 5,7,8 Sentinel lymph node biopsy is currently recommended for patients with melanomas that have a Breslow depth 41 mm or r1 mm when there is ulceration or Clark's level IV or V invasion. 9 Both greater Breslow depth and metastatic melanoma in sentinel lymph nodes are associated with a worse prognosis.…”
mentioning
confidence: 99%